El portafolio como estrategia de evaluación en el proceso de enseñanza y aprendizaje de la física en los estudiantes de tercero de Bachillerato de la “Unidad Educativa Fiscomisional Nuestra Señora del Rosario” - Chamba Medina, Andrés Eduardo (2024)
In the subject of physics, students have difficulties when they are evaluated, therefore, it is important that teachers know how to implement appropriate evaluation strategies. In view of this, the main objective of this research was to propose the portfolio as an evaluation strategy in the teaching and learning process of physics in third year high school students of “Unidad Educativa Fiscomisional Nuestra Señora del Rosario". In this sense, the type of research is field research, with a mixed approach, where information was obtained through a questionnaire applied to teachers of the institution, in addition, the bibliographic review was considered through the use of the search log and mixed cards. The results show that the portfolio has a great importance and presents characteristics that are useful in the evaluation process, also, it is evident that most of the teachers surveyed opt for a qualitative evaluation approach. It is concluded that the portfolio is a strategy to be considered to evaluate competencies of students considering their imagination, creativity, reflection and self-improvement. Keywords: portfolio, evaluation strategy, qualitative evaluation, physics.